2021
DOI: 10.1002/pc.26048
|View full text |Cite
|
Sign up to set email alerts
|

A review on polyaniline composites: Synthesis, characterization, and applications

Abstract: Polyaniline (PANI) is one of the most studied intrinsically conducting polymers. Polyaniline inclusion with different porous materials is a very attractive research area. In this review, the preparation, properties, and applications of PANI composites have been summarized. PANI was found to be promising among the other conducting polymers and incorporated with different materials like graphene, graphene oxide, metal oxide, carbon, carbon nanotube, silica, silicon dioxide, biomolecules, and metal organic framew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(54 citation statements)
references
References 192 publications
(103 reference statements)
0
54
0
Order By: Relevance
“…The most accepted model states that conducting polymers promote intelligent selfhealing due to the electrochemical inhibition and cathodic protection. 32,[34][35][36][37][38] Nonetheless, there is still a scarcity of research articles to demonstrate the underlying anticorrosive mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The most accepted model states that conducting polymers promote intelligent selfhealing due to the electrochemical inhibition and cathodic protection. 32,[34][35][36][37][38] Nonetheless, there is still a scarcity of research articles to demonstrate the underlying anticorrosive mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The color change associated with PANI in different oxidation states can be used in sensors and electrochromic devices [37]. The best method for making a PANI sensor is arguably to take advantage of the dramatic conductivity changes between the different oxidation states or doping levels [38].…”
Section: Polyanilinementioning
confidence: 99%
“…PANI appears white/clear or colorless if the polymer form is leucoemeraldine, and if the polymer type is pernigraniline, it gives blue to violet color, and if the polymer form is emeraldine, it gives blue color if it is basic and gives green color if it is salt form. PANI also has good electrical conductivity only in the emeraldine form, and the other types do not show significant conductivity [37]. As for solubility, all forms of PANI are insoluble in water, acetone, ethanol, and other solvents, but are soluble in dimethylformamide, dimethyl sulfoxide, and N-methyl-2-pyrrolidone [37,68,69].…”
Section: Properties Of Panimentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies on rubber polymer composites have been carried out in recent years [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. It is reported that the enhancement in overall attributes of rubber composites depends on the diverse parameters such as the aspect ratio and size of nanofillers, their location in the rubber matrix, the dispersion degree of nanofillers, and the adhesion degree with the elastomer chains [ 11 ].…”
Section: Introductionmentioning
confidence: 99%